"Peaceful workplace" only a myth?: Examining the mediating role of psychological capital on spirituality and nonviolence behaviour at the workplace. Issue 5 (22nd February 2020) - Sarkar, Ayatakshee; Garg, Naval
Abstract : Purpose: Though violence is very much prevalent in modern organizations, unfortunately, researchers and practitioners have given very little attention in creating an organizational culture based on nonviolence. The purpose of this paper is to explore the relationship between individual spirituality and non-violence work behaviour. It also investigates the mediating role of four constructs of psychological capital (hope, optimism, resilience and self-efficacy). Design/methodology/approach: Collected data is subjected to rigorous reliability, validity and common method biasness tests. Further mediation is analyzed with the help of hierarchical regression, Sobel test and bootstrapping estimates. Findings: The results show that all four dimensions of psychological capital partially mediate the relationship of individual spirituality and non-violent behaviour at the workplace. The practical and theoretical implications of the study are also discussed. Research limitations/implications: Although the study produces significant results, it has certain limitations, too, which can be addressed in future research. Firstly, as psychological capital is a state like construct, the responses of the participants may vary from time to time, leading to biases. Secondly, the study is confined only to manufacturing, IT/ITES and financial institutions. It can be duplicated to other sectors as well to assess its generality. Future researchers may adopt both quantitative and qualitative methodology to explore the field. Even experimental research may help to understand these work behaviours. Although the study has been conducted in business organization the purpose is not to limit it to the workplace context. It is relevant to all sectors and across all domains. Practical implications: The findings have revealed individual spirituality as a significant predictor of nonviolence behaviour at the workplace. Thus managers, leaders, policymakers or organizational development practitioners need to facilitate spirituality at the workplace and introduce spiritual-based interventions such as meditation, yoga and several other mindfulness practices. Even organizational training, which is considered to be essential to human resource development, needs to develop a spiritual development program and also to examine the impact of such programs on organizational outcomes (Dent et al., 2005). Organizational interventions that facilitate mindfulness practices, yoga and meditation will enhance nonviolence communication through empathy and compassion-based listening, meaningful dialogues, through connecting employees with universal human values/needs. Social implications: The primary objective of the study is to foster conflict prevention in society rather than conflict resolution. With the help of the study, the authors understand the importance of spiritual intervention and its impact on the elevation of people's values, beliefs and attitudes. Major organisations such as Apple, Google, Amazon, Microsoft and Facebook have already started to develop spiritual interventions at their workplace. It is an excellent time to capitalize on India's rich spiritual tradition that honours unity in diversity. Besides, an organization's facilitation to connect to employee's actions with spiritual values can overcome cultural conditioning that triggers violence and help in making a more meaningful place to work. Thus, impacting the society from a macro perspective. Originality/value: This is one of the pioneer studies that tried to unlock the "black-box" of mechanism through which individual spirituality impacts non-violent work behaviour.